Validating a model for forecasting the project termination phase using existing business cases. Issue 2 (3rd April 2019) - Marthandam, Nithin Saravana; Ng, Ean H.; Calvo-Amodio, Javier; Narwankar, Chinmay; Barroso, Luis A.
Abstract: Studies on project failure and its subsequent termination phase are scarce; studies that use a quantitative approach are almost nonexistent. This is most likely because organizations usually do not collect data on project failures, are unable to share such data, or a combination of both. The contribution of this article is twofold: to (1) showcase a methodology to validate a model using actual business cases and (2) validate a project termination phase forecast model (PTPFM) using the methodology. The model is validated through four business cases, comparing the results from the model to the decisions made in reality.